MODERN INFORMATION SYSTEMS FOR RESEARCH WORKS OF THE PUSHCHINO RESEARCH CENTER OF RAS - Kornilov, V. V.; Isaev, E. A. (Одеські астрономічні публікації, 2012)
The current state of information systems of the Pushchino Research Center of the Russian Academy of Sciences allows us to successfully solve the problems of computational biology.